SUPPLY CHAIN ANALYSIS OF SKIPJACK TUNA (Katsuwonus pelamis): A CASE STUDY OF POLE AND LINE FISHERIES IN SOUTHEAST MINAHASA - Risman Kadir; Munirah Tuli; Alfi Sahri Remi Baruadi (Universitas Mataram, 2026)
This study aims to determine the supply chain of skipjack tuna (Katsuwonus pelamis) caught by pole and line vessels at Belang Port, Southeast Minahasa Regency, using a descriptive survey approach. Involving fishermen, collectors, and retailers as respondents, data was collected through interviews, observation, documentation, and supporting literature review. The results revealed three main marketing channels: (1) directly from fishermen to consumers, (2) fishermen to retailers, and (3) fishermen to collectors and then to retailers. The largest marketing margins are obtained by retailers, while fishermen receive the lowest margins, indicating an imbalance in profit distribution. Marketing efficiency is hampered by limited capital, inadequate infrastructure, limited access to market information, and fishermen's dependence on collectors. To improve fishermen's welfare, this study recommends strengthening fishermen's institutions, improving market access, and training and empowering fishermen in more effective marketing strategies.